(3GdeZfj aj TQM eNJUQ GdNQbjs - (3GdbQTj, GdebOSj, GdLnqeGYjdj, Ke GdOeTbj, GHf bOGeI, YHO Gddg Hf eMeO Hf bOGeI, (B620 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; cJGH GdGYJcGa ; GdGYJcGa aj GddZI GdYQHjI dRhe GdTjA hMHS GdfaS Ydjg HQG cGf Ch ZjQg s
(3BNQgG (B:s
(3hjfJgj YfO bhdg (B: (3aUd (B: (3hjcQg GdHjY hGdTQGA aj GdeTLO hHg bGd ESMGb deG Qhj CHh gQjQI ef cJGH GdHjhYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 227s
(3cTa GdXfhf (B2 / 1625s
(3TPQGJ GdPgH (B5 / 88s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs